Analisis Sistem Akuntansi Penggajian Pegawai Negeri Sipil Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Langkat - Prisna, Nila Dera; Kusmilawaty, Kusmilawaty (Lembaga Riset Ilmiah, 2022)
The Department of Population and Civil Registration of Langkat Regency is a government agency engaged in population administration and civil registration services. In carrying out their duties, Civil Servants receive a salary for their performance. Matters that include the payroll accounting system are related to employee payroll issues. The method used in this research is descriptive qualitative method where this method only focuses on the civil servant payroll accounting system at Disdukcatpil Langkat Regency. The results in this study show that the payroll accounting system at Disdukcatpil Langkat Regency is good, salary payments are paid regularly every month in accordance with the basic salary obtained along with allowances and deductions. The scale used is a double scale whose salary system is determined not only on the basis of rank but on the results of the work he does and his job responsibilities